Epidemiological evaluation of glanders in Brazil (Research, Society and Development, 2021)
This study was developed to analyze the epidemiological profile of glanders in Brazil from 2010 to 2019. A cross-sectional, descriptive, retrospective and qualitative-quantitative study was carried out using all Brazilian states as units of analysis. The sample was delimited to the period from 2010 to 2019, and data referring to notified cases of glanders were collected from information available in the official database, namely, year, semester, federation unit, total number of cases and total number of outbreaks. In the period, 1398 cases of the disease were reported in Brazil. Acre and Amapá did not report its occurrence, whereas Pernambuco, followed by Mato Grosso and São Paulo, led the absolute number of cases. The states with the highest prevalence were Amazonas (2.59/1000 head), Rio Grande do Norte (2.10/1000 head) and the Federal District (1.94/1000 head). The north region showed the lowest concentration of cases per focus (1.45), and the southeast region the highest (2.73). In conclusion, Brazil has a low prevalence of glanders, with a higher concentration of cases and outbreaks occurring in the northeast region and a higher prevalence in the state of Amazonas. Due to the importance of glanders for public health, measures of active surveillance of the disease in animals and prevention actions, in the One Health context, must be implemented.